(untitled) - Steiner, George Albert (Boston, 2006)
Business, Government and Society, by Steiner and Steiner, was one of the very first books in this course area and has benefited greatly from the reputation of its authors. George Steiner, the father in this father-and-son team, is one of the pioneers in the field. The text includes coverage of all the distinct content areas and is known for its inclusion of historical background. Each chapter has three elements; (1) a beginning story to illustrate central themes, (2) explanatory text, and (3) a case study inviting debate about events related to the subject area. One of the most complete on the market, the 10th Edition of Business, Government and Society not only covers the stakeholder theory, but also covers a total of four theoretical models for analyzing the actions and duties of corporations..
Keywords: Industries,Industrial policy,Các ngành công nghiệp,Chính sách công nghiệp; Social aspects,United States,Thuộc về xã hội,Hoa Kỳ; United States,Hoa Kỳ